Numerical model upgrading of a historical masonry palace monitored with a wireless sensor network. (2016) - Pierdicca, Alessio; Clementi, Francesco; Isidori, Daniela; Concettoni, Enrico; Cristalli, Cristina; Lenci, Stefano
Seismic protection and vulnerability reduction are very relevant issues in European regions, such as Italy, characterised by the presence of a large stock of heritage structures. This increased the interest in structural health monitoring as a powerful tool to quantify and reduce uncertainties regarding the structural performance of buildings. Monitoring can be successfully implemented in some cases as an alternative to interventions or to control the medium- and long-term effectiveness of already applied strengthening solutions. Recently, the use of wireless sensor networks (WSN) as a new kind of architecture for structural monitoring systems has been explored. A WSN is usually a flexible solution with minor costs associated, especially if the network is composed by cheap devices. In this framework, this work details the main results obtained in the context of the 'Palazzo Comunale di Castelfidardo' monitoring project with WSN, with the aim to get an accurate numerical model (NM) that simulates the dynamic behaviour of the whole structure. An iterative approach to perform the manual tuning of the NM is proposed, using as calibration parameters not only mechanical entities, but also boundary conditions. Finally, a comparison between the structural responses, obtained with experimental analysis, and the updated NM is provided.